#### Answer

$y' = -x^{2}sinx $

#### Work Step by Step

$y = x^{2}cosx - 2xsinx -2cosx$
$y' = 2xcosx -x^{2}sinx - 2sinx - 2xcosx +2sinx$
$y' = -x^{2}sinx $

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = -x^{2}sinx $

$y = x^{2}cosx - 2xsinx -2cosx$
$y' = 2xcosx -x^{2}sinx - 2sinx - 2xcosx +2sinx$
$y' = -x^{2}sinx $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.